Integration of Face Detection and Augmented Reality into Human Anatomy Education (International Conference on Computers in Education, 2020)
This paper proposes an interactive augmented reality (AR) application to aid medical student in learning the human anatomy. Students will be able to take a photo of their friend using the camera in real time. Then, the system will detect their friend’s face and relocate the human anatomy to the approximate position of their friends inside the augmented reality application. With this application, the learning process will be fun and could help in improving the student’s retention in their studies while boosting their motivation in getting better in their learning. Besides, teamwork will be fostered along when the students are learning in a group. The experiment is conducted on the first-year medical related student in Universiti Tunku Abdul Rahman (UTAR). The result shows that there are 75% of the students agree and strongly agree that this application is able to facilitate them in the understanding of human anatomy. Based on the survey, it is concluded that the students are satisfied with this application and agreed to the effectiveness of Augmented Reality in their learning process.